2016
DOI: 10.18408/ahuri-5105201
|View full text |Cite
|
Sign up to set email alerts
|

Housing assistance need and provision in Australia: a household-based policy analysis

Abstract: AHURI is a national independent research network with an expert not-for-profit research management company, AHURI Limited, at its centre. AHURI has a public good mission to deliver high quality research that influences policy development to improve the housing and urban environments of all Australians. Through active engagement, AHURI's work informs the policies and practices of governments and the housing and urban development industries, and stimulates debate in the broader Australian community. AHURI undert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

6
4

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 12 publications
1
37
0
Order By: Relevance
“…Existing reviews of tenancy access and management, particularly from the perspective of lowincome renters, have focused on affordability barriers, arrears, evictions and sustaining tenancies (Beer, Slatter et al 2006;Stone, Sharam et al 2015;Stone, Parkinson et al 2016) and the provision of and effectiveness of small scale private rental brokerage and head leasing programs in responding to these issues (Jacobs, Natalier et al 2005;Parkinson 2015;Tually, Slatter et al 2016;Parkinson and Parsell 2018). Other research has revealed the long term persistence of discrimination and tenancy management practices among landlords and agents that adversely impact upon the maintenance of tenancy standards and rights to secure occupancy (Short, Minnery et al 2006;Short, Seelig et al 2008;Hulse, Milligan et al 2011;Nelson, MacDonald et al 2015;MacDonald, Nelson et al 2016).…”
Section: Existing Research On Australian Prs Access and Managementmentioning
confidence: 99%
“…Existing reviews of tenancy access and management, particularly from the perspective of lowincome renters, have focused on affordability barriers, arrears, evictions and sustaining tenancies (Beer, Slatter et al 2006;Stone, Sharam et al 2015;Stone, Parkinson et al 2016) and the provision of and effectiveness of small scale private rental brokerage and head leasing programs in responding to these issues (Jacobs, Natalier et al 2005;Parkinson 2015;Tually, Slatter et al 2016;Parkinson and Parsell 2018). Other research has revealed the long term persistence of discrimination and tenancy management practices among landlords and agents that adversely impact upon the maintenance of tenancy standards and rights to secure occupancy (Short, Minnery et al 2006;Short, Seelig et al 2008;Hulse, Milligan et al 2011;Nelson, MacDonald et al 2015;MacDonald, Nelson et al 2016).…”
Section: Existing Research On Australian Prs Access and Managementmentioning
confidence: 99%
“…A related body of work illuminates the complex interaction of income poverty with high housing costs, limited supply of affordable housing within the private rental sector as well as a geographical mismatch between available rental housing and the employment/educational needs of would-be occupants (Hulse, Reynolds et al 2015). In what they term a 'tenure neutral' analysis, Stone, Parkinson et al (2016) analysed the interaction of housing costs and income on potential housing pathways and housing options of lower income households in receipt of income support including housing assistance (such as Rent Assistance) in comparison with low income households not in receipt or eligible for housing assistance. Their findings illustrate key 'sticking' points within housing pathways as well as drawing attention to households potentially residualised to informal spheres of rental markets, which are the least well regulated.…”
Section: Figure 1: Mobility Into Within and Out Of Social Housingmentioning
confidence: 99%
“…Lack of supply of social housing and long waiting lists, coupled with sometimes-significant step-up in rents and reduced security and rights in the private rental market contribute to reduced transition out of social housing and along the housing continuum (Stone, Parkinson et al 2016).…”
Section: Stability Problemsmentioning
confidence: 99%